An Overall Comparison of Small Molecules and Large Biologics in ADME Testing - Hong Wan (ADMET and DMPK, 2016)
Biologics mainly monoclonal antibodies (mAbs) and antibody-drug conjugates (ADCs) as new therapeutics are becoming increasingly important biotherapeutics. This review is intended to provide an overall comparison between small molecules (SMs) and biologics or large molecules (LMs) concerning drug metabolism and pharmacokinetic (DMPK) or associated with absorption, distribution, metabolism and elimination (ADME) testing from pharmaceutical industry drug discovery and development points of view, which will help design and conduct relevant ADME testing for biologics such as mAbs and ADCs. Recent advancements in the ADME for testing biologics and related bioanalytical methods are discussed with an emphasis on ADC drug development as an example to understand its complexity and challenges from extensive in vitro characterization to in vivo animal PK studies. General non-clinical safety evaluations of biologics in particular for ADC drugs are outlined including drug-drug interaction (DDI) and metabolite/catabolite assessments. Regulatory guidance on the ADME testing and safety evaluations including immunogenicity as well as bioanalytical considerations are addressed for LMs. In addition, the preclinical and human PK data of two marked ADC drugs (ADCETRIS, SGN-35 and KADCYLA, T-DM1) as examples are briefly discussed with regard to PK considerations and PK/PD perspectives.